Success Motivational Videos on social media: A Study of Persuasion - Ali , Youssra Qassim (Zanco Journal of Human Sciences, 2025)
Persuasion is the act by which a side tries to convince or influence another to adopt certain idea or attitude as their core belief system. Persuasion is an effective act that reflects on the life of individuals and on communities in general as it works on modifying and changing thoughts and feelings. Social media seems to be introducing a lot of persuasive contents. Short motivational videos are some of the most trending contents of those kinds on social media. This study randomly selects number of such videos(eight), specifically the ones which tackle the theme of success and how to be successful. The study aims at examining the stylistic means and devices of persuasion in those videos. It specifically seeks to answer the following questions: (i) what are the main rhetorical persuasive appeals used in those videos and which one of them is most commonly used? (ii) Which persuasive devices, among those introduced by Bueuer and Napthine (2008), are more commonly utilized than the others? And (iii) what purposes does each variety of persuasive style serve?